VILJOEN, Marais Inventory of documents - VILJOEN, Marais (ARCA, 2018)
Private papers of M. Viljoen, National Party MPC [1949-1953], MP Alberton [1953-1975], Deputy Minister Labour and Mines [1958-1961], Interior Labour and Immigration [1961], Labour and Immigration [1961-1962], Interior Education Arts and Science Labour Immigration [1962-1966], Minister Labour [1966-1976], Coloured Affairs [1966-1970], Rehoboth Affairs [1969-1970], Interior [1970], Posts and Telegraphs [1970-1974], Post and Telecommucation [1974-1976], Senator [1976-1979], State President [1979-1984].
COVERAGE 1935-1976; 339 Files; 6,89 Metres. AUDIO CASSETTES IN ARCA COLLECTION = 6
Keywords: VILJOEN, Marais; Inventories; Politicians; National Party